A case study: applying Lean Six Sigma concepts to design a more efficient airfoil extrusion shimming process. (18th April 2011) - Hardeman, Claiborne; Goethals, Paul L.
When the objective of the manufacturer is to eliminate waste or create a more efficient process, innovative techniques are often sought for process improvement. The statistical tools used by Six Sigma practitioners are specifically designed for this purpose; they are frequently used to address problems across a wide number of production systems. Each manufacturing application, however, brings a unique array of potential causes and effects that must be considered to properly model process behaviour. This paper specifically examines a shimming process for a mechanically-driven screw press, whereby compressor airfoils (blades) are produced for a gas turbine. To enhance product quality and identify improvements in process performance, the five-phase approach to problem solving used in Six Sigma projects is applied. As a result of the changes implemented in this case study, the product defect level is reduced by as much as 94% and the Six Sigma rating is increased from 0.868 to 3.207.